Primary Squamous Cell Carcinoma of the Parotid Gland: Study and Review of the Literature - Horáková, Zuzana; Stárek, Ivo; Kalfert, David; Dostalova, Lucie; Kalivoda, Ivan; Salzman, Richard (In vivo (Athens, Greece), 2024)
BACKGROUND/AIM: Primary squamous cell carcinoma of the parotid gland (pPSCC) is a rare tumor, accounting for less than 3% of all parotid carcinomas. There is no general consensus on the management of this tumor, since clinical experience for pPSCC is minimal. Moreover, pPSCC is often misdiagnosed for metastatic cutaneous carcinoma. In our study, we focused on evaluating its biological and clinical characteristics, treatment results and prognosis. We proposed an update on diagnostic and therapeutic management of pPSCC. PATIENTS AND METHODS: The retrospective cohort included 18 patients diagnosed and treated for pPSCC in three tertiary head and neck centers between 2008 and 2022. We retrospectively evaluated their prognosis and established a therapeutic recommendation after analyzing our own and previously published data. RESULTS: Fourteen of 18 tumors were diagnosed in stage IV. Five-year overall survival was 36 months. Six patients received palliative therapy. Twelve patients underwent parotidectomy, neck dissection, and adjuvant radiotherapy. Remission was achieved in 8 patients (follow-up interval 3-56 months). One patient died with recurrent disease. The others are alive and in complete remission. CONCLUSION: The definitive diagnosis of pPSCC must meet the histological and clinical criteria. First of all, the metastatic origin of the tumor must be excluded. Five-year survival of this very aggressive tumor does not exceed 50%. Without surgery, the prognosis is poor. The best results, irrespective of tumor stage, are achieved with surgery. Therefore, a total parotidectomy, neck dissection (therapeutic or elective) and adjuvant radiotherapy are indicated for all resectable tumors.
Keywords: squamous cell carcinoma; retrospektivní studie; spinocelulární karcinom; nádory kůže; staging nádorů; Humans; Parotid Gland; Neoplasm Staging; Carcinoma, Squamous Cell; Skin Neoplasms; lidé; Parotid gland; Retrospective Studies; salivary tumor; parotis